Johnson's Quebec, of the dominion of Canada. - Johnson, A. J. (Alvin Jewett), 1827-1884 (A.J. Johnson, 1867)
Map of northeast Canada, which includes New Brunswick, Nova Scotia, and the Island of Anticosti. Relief shown by hachures. Scale [1:1,543,000].